(untitled) (Quest Journal of Management and Social Sciences, 2025)
Background: Labor markets in developing countries often face structural challenges, including limited opportunities, informality, and rising inequalities, that push many young people to migrate in search of better livelihoods. As social protection systems evolve, they increasingly shape migration decisions by reducing risks, supporting mobility, and influencing how youth respond to labor market constraints. Purpose: In South Asia, labor potential exceeds fragile market structures, nudging migration. The study aims to consolidate fragmented research across labor, migration, and social policy, providing an integrated understanding of how welfare mechanisms influence migration decisions and labor mobility. Methodology: A bibliometric analysis was done using the Scopus database (1991–2024), following the PRISMA framework for systematic selection of studies. Initially, there were 556 records; only 254 peer-reviewed articles met the inclusion criteria. Using the VOS viewer and the bibiloshiny package in R, co-authorship networks, keyword co-occurrence, and citation structures were mapped to identify intellectual patterns and thematic evolution. Findings: The bibliometric analysis shows a shift from theoretical debates on globalization and market flexibility to applied studies on migration, informality, and social protection. The collaboration pattern is fragmented but gradually expanding, signaling potential for stronger global and interdisciplinary engagement. Post-2022 research, shaped by the COVID-19 crisis, emphasizes inequality, resilience, and marginalized labor, redefining social protection as a proactive and adaptive mechanism for inclusive labor systems. Conclusion: Social protection emerges as both stabilizing and enabling, shaping migration through risk minimization and behavioral incentives. The field is maturing toward an integrated labor–migration framework, though regional and conceptual gaps persist. Keywords: Labor migration, social protection, Youth employment, Bibliometric analysis, South Asia